Influence of Fungal Colonization on Exacerbations in Patients with Cystic Fibrosis - Claudia Janeth Madrid-Carbajal; Teresa Peláez-García de la Rasilla; Marta Iscar-Urrutia; Marta Solís-García; Ramón Fernández-Álvarez; Liliana Pérez-Martínez; María Soledad Zapico-González; Marta Garcia-Clemente (Journal of Fungi)
The importance of fungal pathogens in cystic fibrosis (CF) patients and their diagnosis remains a challenge, so our aim was to analyze the influence of the detection of fungi in sputum by using conventional culture and molecular techniques, polymerase chain reaction (PCR), lateral flow devices (LFDs), and galactomannan (GM) on exacerbations in patients with cystic fibrosis. A prospective study was conducted in patients via follow-up in the CF Unit of the Central University Hospital of Asturias from January 2021 to April 2022. Adult patients with at least one documented exacerbation were included. A complete fungal analysis of sputum samples was performed both in a period of clinical stability and in the exacerbation period. The microbiological study included conventional cultures for fungi, qPCR (polymerase chain reaction), LFDs (lateral flow devices), and galactomannan (GM) in sputum. We found that there were changes in their detection according to whether the patient is in a period of clinical stability or exacerbation; the positivity of the molecular tests and biomarkers in the period of exacerbation increased by 14%, 25%, and 21% for the analysis by qPCR, GM, and LFDs for Aspergillus and by 15% for the sputum culture for Aspergillus, which may mean that fungal isolates may play a role in the exacerbations of these patients.